Pengaruh Persepsi Manfaat Dan Persepsi Kemudahan Terhdap Keputusan Penggunaan BNI Tapcash Di Penggemar NCTZEN Pada Grup Facebook - Sugiarti, Riri; Suherman, Enjang; Khalida, Laras Ratu (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The payment system has undergone transformation due to technological advances in the financial industry, especially with the introduction of e-money or electronic money. PT. Bank Negara Indonesia, the entity responsible for issuing banknotes in Indonesia, promotes its products under the BNI TapCash brand. The main purpose of this study is to analyze and determine the perception of benefits and perceptions of convenience in the decision to use BNI TapCash. This study uses a verifiative descriptive methodology with a quantitative approach. The methodology used is multiple linear regression techniques. The population sample of this study consisted of 102,706 BNI TapCash registered users in Indonesia who are members of the Nctzen Indonesia Facebook page. A sample of 104 people was selected using a random sampling approach known as direct random selection. The participants were BNI TapCash users who were given questionnaires to collect primary data. Data and related discussions display the perception of benefits and perceptions of convenience from BNI TapCash have a considerable influence on its utilization decisions. This can mean that users tend to use BNI TapCash when they have a positive perception of the convenience and benefits provided by the system.